The Critical Role of Tryptophan in the Antimicrobial Activity and Cell Toxicity of the Duck Antimicrobial Peptide DCATH - Feng, Xingjun; Jin, Sanjun; Wang, Min; Pang, Qian; Liu, Chunlong; Liu, Ruiqi; Wang, Yingjie; Yang, Hao; Liu, Fangju; Liu, Yueying (Frontiers in Microbiology, 2020)
Antimicrobial peptides (AMPs) have attracted more attention for their potential candidates for new antibiotic drugs. As a novel identified cathelicidin AMP from duck, dCATH owns broad-spectrum antimicrobial activities but with a noticeable toxicity. To explore dCATH-derived AMPs with reduced cell toxicity and improved cell selectivity, a series of truncated and tryptophan-replaced peptides of dCATH were designed. Two truncated peptides containing one of the two tryptophan (Trp) residues at the positions of 4 and 17 (W4 and W17) of dCATH, dCATH(1-16) and dCATH(5-20), showed strong antibacterial activity, but didn’t show obvious hemolytic activity and cytotoxicity. The derived peptides not containing Trp didn’t possess obvious antimicrobial activity, and their hemolytic and cytotoxic effect was also diminished. Also as evidence by Trp fluorescence experiment that existence of W4 and W17 was crucially important to the antimicrobial activity, hemolysis and cytotoxicity of dCATH, and one of the two Trp residues was competent and necessary to retain its antimicrobial activity. Antibacterial mechanism analysis showed that dCATH(1-16) and dCATH(5-20) killed bacterial cells by increasing permeability and causing a loss of membrane integrity. dCATH(1-16) and dCATH(5-20) possessed insignificant inhibitory activity against levels of IL-6, TNF-α and NO in RAW 264.7 cells treated with LPS. In vivo, intraperitoneal administration of the two peptides significantly decreased mortality and provided protection against LPS-induced inflammation in mice challenged with lethal dose of LPS. The two peptides, dCATH(1-16) and dCATH(5-20), which possessed high antibacterial activity and cell selectivity, may herald development prospects as new antibacterial agents in the future.